Tailoring gut immune responses with lipoteichoic acid-deficient Lactobacillus acidophilus - Lightfoot, Yaíma L.; Mohamadzadeh, Mansour (Frontiers in Immunology, 2013)
As highlighted by the development of intestinal autoinflammatory disorders when tolerance is lost, homeostatic interactions between gut microbiota, resident immune cells, and the gut epithelium are key in the maintenance of gastrointestinal health. Gut immune responses, whether stimulatory or regulatory, are dictated by the activated dendritic cells (DCs) that first interact with microorganisms and their gene products to then elicit T and B cell responses. Previously, we have demonstrated that treatment with genetically modified Lactobacillus acidophilus is sufficient to tilt the immune balance from proinflammatory to regulatory in experimental models of colitis and colon cancer. Given the significant role of DCs in efficiently orchestrating intestinal immune responses, characterization of the signals induced within these cells by the surface layer molecules, such as lipoteichoic acid (LTA), and proteins of L. acidophilus is critical for future treatment and prevention of gastrointestinal diseases. Here, we discuss the potential regulatory pathways involved in the downregulation of pathogenic inflammation in the gut, and explore questions regarding the immune responses to LTA-deficient L. acidophilus that require future studies.